Different Morphology of Neuritic Plaques in the Archicortex of Alzheimer's Disease with Comorbid Synucleinopathy: A Pilot Study - Jankovska, Nikol; Olejar, Tomas; Kukal, Jaromir; Matej, Radoslav (Current Alzheimer research, 2020)
BACKGROUND: Bulbous neuritic changes in neuritic plaques have already been described, and their possible effect on the clinical course of the disease has been discussed. OBJECTIVE: In our study, we focused on the location and density of these structures in patients with only Alzheimer's disease (AD) and patients with AD in comorbidity with synucleinopathies. METHODS: Utilizing immunohistochemistry and confocal microscopy, we evaluated differences of neocortical and archicortical neuritic plaques and the frequency of bulbous changes in the archicortex of 14 subjects with Alzheimer's disease (AD), 10 subjects with the Lewy body variant of Alzheimer's disease (AD/DLB), and 4 subjects with Alzheimer's disease with amygdala Lewy bodies (AD/ALB). Also, the progression and density of neuritic changes over the time course of the disease were evaluated. RESULTS: We found structural differences in bulbous dystrophic neurites more often in AD/DLB and AD/ALB than in pure AD cases. The bulbous neuritic changes were more prominent in the initial and progressive phases and were reduced in cases with a long clinical course. CONCLUSION: Our results indicate that there is a prominent difference in the shape and composition of neocortical and archicortical neuritic plaques and, moreover, that bulbous neuritic changes can be observed at a higher rate in AD/DLB and AD/ALB subjects compared to pure AD subjects. This observation probably reflects that these subacute changes are more easily seen in the faster clinical course of AD patients with comorbidities.
Keywords: Male; amyloidní plaky; bulbous neuritic changes; pilotní projekty; synukleinopatie; Alzheimerova nemoc; Alzheimer Disease; archicortex; Aged; imunohistochemie; mužské pohlaví; senioři; neurity; Synucleinopathies; synucleinopathy; Neurites; Hippocampus; Plaque, Amyloid; lidé; ženské pohlaví; Immunohistochemistry; neocortex; Humans; Alzheimer`s disease; Pilot Projects; Female; hipokampus; neuritic plaques